Pengembangan Bahan Ajar IPA Berbasis SETS pada Materi Sistem Pencernaan untuk Meningkatkan Literasi Sains Siswa SD: Development of SETS-Based Science Teaching Materials on the Digestive System to Enhance Science Literacy among Elementary School Students - Aigadilla Anugrah; Ashar Hasairin; Aswarina Nasution; Nurfajriani Nurfajriani; Wawan Bunawan; Zuraida Lubis (ITScience (Information Technology and Science), 2026)
The state of science education in Grade V at SDN 105855 PTPN II Tanjung Morawa indicates that students' scientific literacy remains low, and there is limited use of instructional media that connect scientific concepts with everyday realities. Consequently, students have not fully grasped the interrelationships among science, the environment, technology, and social contexts within daily life. This study employed a Research and Development (R&D) approach utilising the ADDIE model—comprising the stages of Analysis, Design, Development, Implementation, and Evaluation. The trial involved 25 students from class VA. Findings reveal that the designed instructional material achieved excellent validity ratings. Expert assessments recorded validity scores of 92.42% from the subject matter expert, 84.33% from the media expert, and 80.00% from the language expert. Regarding practicality, feedback from both teachers and students fell into the